Geology, Geochemistry and Geophysical Studies in Exploration of Copper and Iron Reserves: A Case Study - Motlagh , Zohreh Kazemi; Rasti, Arezou; Safaei, Siam (Technium EcoGeoMarine, 2022)
The large Miocene stock work-vein porphyry copper mineralization of Sarcheshmeh are already known, but there are still few studies regarding mineral prospection in smaller deposits. This paper proposes exploration techniques for Cu prospecting in Hefdah Chenar area, Kerman Province, Iran, as case study. This study investigate the Hefdah Chenar area’s mineralization in light of its natural context, focusing on geology, geochemistry, and geophysics. Hefdah Chenar district consists of an Eocene volcanic andesite succession with a gently northeast dipping, which was intruded by at least two phases of copper-bearing granodiorite porphyries. Several documents and data including topographic, geological, land use, soils maps, Hefdah Chenar area’s map, field visit, the geochemical study’s results, and stream sediment samples proved the presence of some points with a grade higher than the threshold limit. The results of the geophysical IP&RS method indicated that the sulfur mineralization trend was northeast and consistent with the effects of surface mineralization. The result of this investigation indicates that based on the results of geophysical models, there is an increase in the amount of induced polarization at the location of possible faults. Furthermore, among these, magnetic data presents that there is no significant changes except in areas with magnetic veins.